ANALISIS TINGKAT PEMAHAMAN DAN MISKONSEPSI MAHASISWA PGMI PADA MATERI MORFOLOGI TUMBUHAN MELALUI PEMBELAJARAN BERBASIS PRAKTIKUM - Tekisha Laila Fitria; Izzatin Kamala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A solid understanding of concepts is an essential competency that PGMI students, as prospective teachers, must possess. However, misconceptions regarding plant morphology are still likely to occur and can affect the learning process. This study aims to analyze the level of understanding and misconceptions among PGMI students regarding plant morphology through laboratory-based learning. The study employed a quantitative descriptive method involving 30 PGMI students. Data were collected using the Three-Tier Diagnostic Test, which consists of 10 items. The results showed that 69.0% of the students’ responses fell into the “conceptual understanding” category, 17.0% indicated misconceptions, 12.3% indicated a lack of conceptual understanding, and 1.7% were guesses or errors. The highest incidence of misconceptions was found in the subconcepts of the root system, stem modifications (rhizomes), and flower parts, each accounting for 23.3%. The results indicate that most students have a good understanding of plant morphology concepts, although misconceptions were still found in certain subconcepts. Therefore, laboratory activities need to be continuously optimized to strengthen conceptual understanding and minimize misconceptions among prospective elementary school teachers.